2012
DOI: 10.7314/apjcp.2012.13.11.5463
|View full text |Cite
|
Sign up to set email alerts
|

Use of ALLGIO Probe Assays for Detection of HBV Resistance to Adefovir in Patients with Chronic Hepatitis B, Kerman, Iran

Abstract: Hepatitis B virus (HBV) infection is contagious with transmissiobn vertically or horizontally by blood products and body secretions. Over 50% of Iranian carriers contracted the infection prenatally, making this the most likely route of transmission of HBV in Iran. To evaluate the resistance to adefovir (ADV) therapy in patients with chronic hepatitis B infection, a study was conducted on 70 patients (63 males and 7 females), who had received in first line lamivudine and second line adefovir. All were tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…The other mutations reported in this study have been previously reported in other countries (21, 26-28). We did not observe other reported mutations in Iran, including Q149K, L122F, N118D/T, L157M, H124Y, rtA181T, rtA181S, rtM204I, rtA181T, rtN236, and rtA181V (25,29,30).…”
Section: Discussioncontrasting
confidence: 80%
“…The other mutations reported in this study have been previously reported in other countries (21, 26-28). We did not observe other reported mutations in Iran, including Q149K, L122F, N118D/T, L157M, H124Y, rtA181T, rtA181S, rtM204I, rtA181T, rtN236, and rtA181V (25,29,30).…”
Section: Discussioncontrasting
confidence: 80%
“…The viral infections cause many deaths in many parts of the world. Hepatitis B virus (HBV) infection is also one of those viral diseases and a major public health problem [1]. HBV can cause a variety of diseases in humans from inactive carriers to progressive liver disease, including chronic hepatitis B, cirrhosis and hepatocellular carcinoma (HCC) [2].…”
Section: Introductionmentioning
confidence: 99%